ChemInform Abstract: Metabolic Glycoengineering with N‐Acyl Side Chain Modified Mannosamines. Issue 39 (September 2016) - Wratil, Paul R.; Horstkorte, Ruediger; Reutter, Werner
Abstract: Review: 428 refs.